A guide for construction practitioners to integrate robotic systems in their construction applications - Prieto, Samuel A.; Xu, Xinghui; García de Soto, Borja (Frontiers in Built Environment, 2024)
The use of robots can boost productivity and reduce costs in construction projects. However, choosing the right robotic platform for the right application can be challenging, costly, and time-consuming. This paper presents a guide for researchers and construction practitioners interested in using robotic systems. This guide is meant to assist in developing a flexible open platform that can be customized to the specific requirements needed. A methodology covering the different aspects to be considered when it comes to a robotic platform, such as the framework (both hardware and software), the environment the robot is going to be operating, the level of supervision (i.e., autonomy) the robot requires, different hardware required on board (i.e., sensors and computers), and the control strategies and systems and communication network is presented. The methodology is implemented with a practical application where a semi-autonomous robotic system is designed and developed with the simple goal of data collection on construction sites, making sure that all the steps covered in the methodology are addressed. The results show that the methodology is applicable to a wide range of solutions, with a focus on the development of the platform itself and not the final application.